Experimental study on the diffusion process of natural gas from buried pipelines to underground confined spaces - Xuemei Wang; Tianlai Hou; Wenxue Gao; Kecheng Yu; Tiantian Zhang; Yufei Tan (Natural Gas Industry B)
In recent years, leakage from buried gas pipelines has been a frequent occurrence around the world. Leaked gas can quickly diffuse and accumulate in adjacent confined spaces, such as inspection wells, sewage pipes, and heat pipeline trenches, posing serious threats to people's lives and property in the event of fire. In this study, a large-scale experimental system was conducted to better understand how methane diffuses after an unintended leak from an underground pipe and how long the methane may take to dissipate in the soil and the adjacent underground confined space. A theoretical analysis is conducted of the seepage characteristics of methane gas in soil, and the experimental results indicate that the variation of methane concentration over time in soil and underground confined spaces is directly related to the distance between the test points and the leak holes. With an escalation in the gas flow rate, methane concentration progressively elevates within the same leakage time, demonstrating a decreasing augmentation rate. Once the air source has been cut off, the gas concentration in the underground confined space will maintain a stable state for a period time after reaching the peak value. Additionally, the time required to reach the lower and upper limits of dangerous concentration has an exponential relationship with the diffusion distance. Fitting curve equations have been drawn in all experimental scenarios.